PROFESSIONAL ZAKAT ON PERFORMANCE ALLOWANCES AMONG PTKIN SENIOR LECTURERS: POTENTIAL AND DISTRIBUTION CHARACTERISTICS - Mayyadah; Syaakir Sofyan; Fani Ramadhani; Muhammad Syarif Nurdin (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to analyze the potential and characteristics of zakat on performance-based allowances for professors and associate professors at PTKIN institutions, particularly at UIN Datokarama Palu. The research design employed was qualitative field research. The research subjects consisted of 6 full professors and 6 associate professors selected through a total sampling technique. Data were collected through in-depth interviews, observations, and documentation, and analyzed using the Miles & Huberman model through the stages of data reduction, data presentation, and conclusion drawing. The research findings indicate that lecturers’ performance-based allowances constitute a significant potential source for strengthening Islamic philanthropy and educational financing within PTKIN institutions. In terms of characteristics, professional zakat among senior lecturers reflects a high level of zakat awareness, primarily motivated by religious obligation and a sense of social responsibility. The selected mustahik are predominantly the poor and those categorized as fī sabīlillāh, particularly university students, Islamic boarding schools, mosques, and Islamic educational institutions. Meanwhile, zakat payment patterns combine direct distribution with digital payment systems, although social proximity-based distribution remains dominant. This study is limited by the number of informants. Furthermore, the calculation of zakat potential remains an estimate and does not fully reflect the actual circumstances of individuals, making it highly dependent on the informants’ perceptions. Nevertheless, the study contributes to the development of professional zakat studies by demonstrating that the remuneration system for lecturers at PTKIN institutions creates substantial zakat potential that can be institutionally optimized.This study offers a novel contribution by specifically examining the potential and characteristics of professional zakat on performance-based allowances among full professors and associate professors at PTKIN institutions, particularly UIN Datokarama Palu. It also integrates analyses of zakat potential, payment characteristics, recipient patterns, and distribution mechanisms within the context of Islamic higher education institutions.